Praxeology as an answer to problems in the philosophy of science - Freire, Lucas (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The general aim of this article is to study how praxeology deals with issues related to the empiricist character of inductivism, logical positivism and falsifiability in the philosophy of Science. A secondary goal is to analyze these approaches based on the discussion that has been taking place in the philosophy of science for decades. Another secondary aim is to popularize the praxeological approach in economics. Praxeology proposes an alternative for economic science – a reply to several problems in the philosophy of science views that have inspired mainstream economics for a long time. It is worthy of consideration on the part of scholars in the field not because it is immune to any kind of criticism, but rather because of its role in the methodological debate, which begs for more careful attention on the part of economists, and, mainly, due to the new issues it has raised.